2017
DOI: 10.4082/kjfm.2017.38.4.173
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Lifestyle Changes on Blood Pressure Control among Hypertensive Patients

Abstract: BackgroundHypertension is highly prevalent among patients who visit primary care clinics. Various factors and lifestyle behaviors are associated with effective blood pressure control. We aimed to identify factors and lifestyle modifications associated with blood pressure control among patients prescribed antihypertensive agents.MethodsThis survey was conducted at 15 hospital-based family practices in Korea from July 2008 to June 2010. We prospectively recruited and retrospectively assessed 1,453 patients presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 20 publications
5
39
6
1
Order By: Relevance
“…Assessment of the hypertension cases in the context of the age revealed that high age leads to increase episodes of hypertension among the Sudanese population. Yang et al (2017) also found similar results on the Korean population highlighting that higher age leads to increased prevalence of hypertension in the world. However, Bruno et al (2016) reported contrary results as it found the most prevalence of hypertension cases in the young adults.…”
Section: Discussionsupporting
confidence: 72%
“…Assessment of the hypertension cases in the context of the age revealed that high age leads to increase episodes of hypertension among the Sudanese population. Yang et al (2017) also found similar results on the Korean population highlighting that higher age leads to increased prevalence of hypertension in the world. However, Bruno et al (2016) reported contrary results as it found the most prevalence of hypertension cases in the young adults.…”
Section: Discussionsupporting
confidence: 72%
“…There was an error in the article, “The effect of lifestyle changes on blood pressure control among hypertensive patients 1) .” The authors found an error after the publication of this work 1) and asked the editorial board to correct it. So we would like to replace Table 3 of the original paper with a revised version.…”
mentioning
confidence: 99%
“…A positive effect of life style modification on blood pressure has also been reported among Korean adults (37,38).…”
Section: Resultsmentioning
confidence: 79%